DARI FOLLOW TURUN KE HATI: Upaya Media Sosial Internal JakunUB Menyentuh Kognisi, Afeksi, dan Konasi Mahasiswa Universitas Bakrie - Nurul, Diana Thasya Sandya (Journal Communication Spectrum : Capturing New Perspectives in Communication, 2015)
The use of internal media as a means of communication between PR practitioners and the internal public can be in various forms. One of them uses social media. In Bakrie University, social media is used as a medium of communication with students, where students have different uniqueness from other stakeholders. Besides being one of the internal public of Bakrie University, students are also customers who need to be served well. This article explores the use of internal social media within Bakrie University by interviewing students and searching online media documents to see the message strategy delivered by JakunUB, one of Bakrie University's internal social media so that the message is able to influence student attitudes on cognitive, affective and conative aspects. The results of the analysis based on message strategy theory, customer relations management (CRM), and message impact theory show that the function and role of internal PR in providing information through JakunUB, can only touch cognitive and conative aspects, while the function of PR CRM through JakunUB in providing services has able to reach three aspects of attitude, namely cognitive, affective and conative. One factor is the number of affective messages that are not as many as cognitive and conative messages. Another factor is that students feel that affective messages conveyed by JakunUB are merely normative information, which cannot yet touch students' emotions. In addition, JakunUB's function as a CRM role tends to be supported by elements of trust that affect student affection, thereby making CRM functions and roles better than internal public relations. That is, JakunUB only works for customer service, not to establish long-term communication and relationships that build emotional ties with internal stakeholders, including students.